2012
DOI: 10.1093/chemse/bjs070
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Chemosensory Traits in Human Twins

Abstract: We explored genetic influences on the perception of taste and smell stimuli. Adult twins rated the chemosensory aspects of water, sucrose, sodium chloride, citric acid, ethanol, quinine hydrochloride, phenylthiocarbamide (PTC), potassium chloride, calcium chloride, cinnamon, androstenone, Galaxolide™, cilantro, and basil. For most traits, individual differences were stable over time and some traits were heritable (h(2) from 0.41 to 0.71). Subjects were genotyped for 44 single nucleotide polymorphisms within an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 35 publications
5
72
1
Order By: Relevance
“…However, the channel is also widely expressed in brain, heart, small intestine, lung (both in fibroblasts and epithelial cells), skeletal muscle, skin (keratinocytes), bladder, prostate, vascular endothelial cells, and pancreas (for a review see . It is also expressed on taste cells, where it associates with the bitter taste receptor TAS2R60 (Knaapila et al, 2012).…”
Section: Ankyrin Transient Receptor Potential Subfamilymentioning
confidence: 99%
“…However, the channel is also widely expressed in brain, heart, small intestine, lung (both in fibroblasts and epithelial cells), skeletal muscle, skin (keratinocytes), bladder, prostate, vascular endothelial cells, and pancreas (for a review see . It is also expressed on taste cells, where it associates with the bitter taste receptor TAS2R60 (Knaapila et al, 2012).…”
Section: Ankyrin Transient Receptor Potential Subfamilymentioning
confidence: 99%
“…Recently, it has been demonstrated that ethanol flavor perception (but not taste) is associated to variants in the olfactory receptor (OR) OR7D4 gene and to the SCNN1D, a gene encoding a subunit of the salt taste receptor. 20 Moreover, Mc Rae et al have demonstrated that a non-synonymous variant of OR2J3, an OR gene, impairs the ability to detect cis-3-hexen-1-ol, a key component in many different foods including wine. 21 Finally, we conducted a study on numerous taste-related genes, which allowed us to associate white wine and vodka liking to variations on the TAS1R2 gene in Central Asia populations, suggesting a general role in ethanol perception for this sweet receptor gene.…”
Section: Introductionmentioning
confidence: 99%
“…To detect these agents, humans have a large and diverse family of taste receptors (named T2Rs), comprising 25 different bitter receptors with genes clustered primarily on chromosomes 7 and 12 (2,3). The sequences, and thus functions, of T2Rs vary across individuals (4). Both cell-based assays and psychophysical studies have shown that single nucleotide polymorphisms (SNPs) 4 in the genes that code for bitter receptors (TAS2Rs) result in different responses to bitter stimuli, such that individuals with one form of a gene can perceive a stimulus as intensely bitter whereas individuals with another form may not perceive its bitterness at all (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%